Guaranteeing Social Enterprises - The EaSI way - Wouter Torfs; Mario Lupoli (European Investment Fund (EIF), 2017)
This report summarises the current state of the external financing markets of the Social Enterprises targeted by the Employment and Social Innovation (EaSI) guarantee program managed by the European Investment Fund (EIF) and funded by the European Commission. The report starts by elaborating on the interpretation of what constitutes a Social Enterprise under the EaSI program. It goes on to provide an overview of the EaSI Social Enterprise sector in Europe and a discussion of its external financing market challenges. It furthermore discusses the initiatives undertaken by the EIF to address the challenges Social Enterprises face on the debt market. While the EIF has booked significant progress towards improving access to finance of Social Enterprises', a rough approximation of the unmet external financing demand on the market reveals that additional efforts are required to further close the social funding gap.
Keywords: 330